Improved skin delivery and validation of novel stability-indicating HPLC method for ketoprofen nanoemulsion - Lucca, Letícia Grolli (2020)
Abstract Ketoprofen is a non-steroidal anti-inflammatory drug (NSAID) widely used to treat rheumatoid arthritis and other inflammatory diseases. Normally used by oral route, this drug presents numerous side effects related to this administration route, such as nausea, dyspepsia, diarrhea, constipation and even renal complications. To avoid that, topical administration of ketoprofen represents a good alternative, since this drug has both partition coefficient and aqueous solubility suitable for skin application, compared to other NSAIDs. In this study, we describe the production of a nanoemulsion containing ketoprofen, its skin permeation and in vitro release study and a novel validation method to analyze this drug in the permeation samples and a forced degradation study using skin and nanoemulsion samples. The new HPLC method was validated, with all specifications in accordance with validation parameters and with an easy chromatographic condition. Forced degradation study revealed that ketoprofen is sensitive to acid and basic hydrolysis, developing degradation peaks after exposure to these factors. Concerning in vitro release from the nanoemulsion, release curves presented first order profile and were not similar to each other. After 8 h, 85% of ketoprofen was release from the nanoemulsion matrix while 49% was release from control group. In skin permeation study, nanoemulsion enabled ketoprofen to pass through the skin and enhanced retention in the epidermis and stratum corneum, layer on which the formulation presented statistically different values compared to the control group.